Three gangliogliomas: results of GTG-banding, SKY, genome-wide high resolution SNP-array, gene expression and review of the literature - Xu, Li-Xin; Holland, Heidrun; Kirsten, Holger; Ahnert, Peter; Krupp, Wolfgang; Bauer, Manfred; Schober, Ralf; Mueller, Wolf; Fritzsch, Dominik; Meixensberger, Jürgen; Koschny, Ronald (Neuropathology, 2015)
According to the World Health Organization gangliogliomas are classified as well-differentiated and slowly growing neuroepithelial tumors, composed of neoplastic mature ganglion and glial cells. It is the most frequent tumor entity observed in patients with long-term epilepsy. Comprehensive cytogenetic and molecular cytogenetic data including high-resolution genomic profiling (single nucleotide polymorphism (SNP)-array) of gangliogliomas are scarce but necessary for a better oncological understanding of this tumor entity. For a detailed characterization at the single cell and cell population levels, we analyzed genomic alterations of three gangliogliomas using trypsin-Giemsa banding (GTG-banding) and by spectral karyotyping (SKY) in combination with SNP-array and gene expression array experiments. By GTG and SKY, we could confirm frequently detected chromosomal aberrations (losses within chromosomes 10, 13 and 22; gains within chromosomes 5, 7, 8 and 12), and identify so far unknown genetic aberrations like the unbalanced non-reciprocal translocation t(1;18)(q21;q21). Interestingly, we report on the second so far detected ganglioglioma with ring chromosome 1. Analyses of SNP-array data from two of the tumors and respective germline DNA (peripheral blood) identified few small gains and losses and a number of copy-neutral regions with loss of heterozygosity (LOH) in germline and in tumor tissue. In comparison to germline DNA, tumor tissues did not show substantial regions with significant loss or gain or with newly developed LOH. Gene expression analyses of tumor-specific genes revealed similarities in the profile of the analyzed samples regarding different relevant pathways. Taken together, we describe overlapping but also distinct and novel genetic aberrations of three gangliogliomas.
Gesehen am 07.07.2020
First published: 06 November 2014